An “in the wild” longitudinal cross-site study of networked public displays user communities through situated snapshots - Memarovic, Nemanja; Schieck, Ava Fatah gen.; Schnädelbach, Holger; Kostopoulou, Efstathia; North, Steve; Ye, Lei (2016)
Networked public displays are a new medium, and as such they can improve the quality and experience of urban spaces by providing new means to engage members of place-based communities. As they are located in different public spaces understanding commonalities and differences between their user communities helps in building a solid foundation for knowledge on how networked public displays operate. In this paper we describe findings from a 12 weeks deployment of the Moment Machine application that allows posting and viewing situated snapshots across 4 displays placed in urban settings of the Screens in the Wild Network. We describe similarities/differences between the four user communities in terms of the photos taken, returning users behavior, interaction session properties etc. Overall, our findings contribute to the buildup of knowledge on general engagement patterns of networked public displays’ user communities. We also suggest that situated snapshots and their analysis as described in this paper can be used as a research tool and methodology for capturing and uncovering the part of a place-based community interested in interacting with public displays.